Transformative leadership adoption assessment a manual for cooperatives. (Quezon City Asian Women Co-operative Development Forum, 2005)
Contents: Glossary. Acronyms about Cooperatives and Transformative leadership to co-operatives. Standards for stages of development and general level of adoptions of transformative leadership. Procedures for the assessment of co-ops' general level of adoption of transformative
Purpose: "It provides a framework and a systematic process of assessing a co-ops' level of adoption of a transformative form of leadership."
With fund support from MISEREOR.
Keywords: Cooperation -- Asia -- Handbooks, manuals, etc; Leadership -- Asia -- Handbooks, manuals, etc